Enhancing Paragraph Writing Proficiency: A Study of Students' Performance Post Global English Textbooks Exposure - Yunus, Muhammad; Dalle, Muhammad Basri; Kaharuddin, Kaharuddin; Hudriati, Andi; Strid, John Evar (International Journal of Language Education, 2024)
The article focuses on identification of students’ performance to write paragraphs and the topics needed by students to be developed post global English textbooks exposure. This study aimed to investigate description of current students’ performance to write paragraphs after studying a paragraph writing using Global English Textbooks and to find out the topics needed by students to be developed as teaching English textbook materials for Paragraph Writing Course. The research employed a mixed-methods approach, combining quantitative analysis of students' paragraph writing performance with qualitative interpretation into their perceptions to the use of global English textbooks as writing paragraph teaching materials. The total samples were 44 students of English Study Program, Faculty of Letters, Universitas Muslim Indonesia. To obtain information from the informants, the researchers employed questionnaires of Paragraph Writing distributed to the students through the Learning Management System (LMS) Google form.  The results showed that students exhibited a wide range of proficiency levels in paragraph writing, from advanced to fundamental deficiencies, necessitating targeted support across all skill levels. Moreover, a significant proportion of students lacked confidence in their writing abilities, emphasizing the importance of tailored instruction to address uncertainties effectively. Challenges with global English textbooks, including language complexity and cultural references, exacerbated these issues. Despite the inherent benefits of paragraph writing, such as language development and critical thinking skills, some students questioned its relevance in non-native English education settings. Additionally, doubts about fundamental language aspects like vocabulary and grammar underscored the need for focused instruction in these areas. Overall, addressing these challenges required comprehensive supports and resources to enhance students' paragraph writing skills and confidence levels effectively. Meanwhile, the exploration of sixty topics provided valuable insights into students' interests and knowledge. Among them, sixteen topics emerged as notably popular, indicating a strong resonance with students. These topics ranged from personal narratives to societal issues, reflecting students' diverse values and concerns. Furthermore, themes related to self-improvement and academic success garnered considerable interest, underscoring students' aspirations for growth. Even less chosen topics still demonstrated students' engagement with various aspects of interpersonal relationships and cultural identity. Moreover, the inclusion of less common topics reflected students' recognition of broader educational and patriotic ideals, albeit with less enthusiasm.